2019
DOI: 10.1039/c9ra06406k
|View full text |Cite
|
Sign up to set email alerts
|

1,1-Difluoroethyl chloride (CH3CF2Cl), a novel difluoroalkylating reagent for 1,1-difluoroethylation of arylboronic acids

Abstract: 1,1-Difluoroethylated aromatics are of great importance in medicinal chemistry and related fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…It was found that the reaction of 2 a with 1 b afforded trace of the desired product and the residual 1 b (determined by GC-MS) (Scheme 3). It should be noted that the result is in sharp contrast to the nickel-catalyzed Suzuki-type reaction, [14] which had similar reaction activity between CH 3 CF 2 Cl and ClCH 2 CH 2 Cl.…”
mentioning
confidence: 62%
See 3 more Smart Citations
“…It was found that the reaction of 2 a with 1 b afforded trace of the desired product and the residual 1 b (determined by GC-MS) (Scheme 3). It should be noted that the result is in sharp contrast to the nickel-catalyzed Suzuki-type reaction, [14] which had similar reaction activity between CH 3 CF 2 Cl and ClCH 2 CH 2 Cl.…”
mentioning
confidence: 62%
“…1,1‐Difluoroethyl chloride (CH 3 CF 2 Cl, HCFC‐142b), an inexpensive and readily available raw material, is regarded as an ideal reagent to synthesis 1,1‐difluoroethyled compounds. Previously, we developed nickel‐catalyzed difluoroethylation of arylboronic acids with CH 3 CF 2 Cl . However, this method needs large excess of CH 3 CF 2 Cl and afforded low product yields due to the homo‐coupling and protodeborylation of arylboronic acids.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the C−Cl bond provides a handle for further product derivatization. The mild reduction to the −CF 2 H unit with H 2 ‐Pd/C, [23] Ni‐catalysed cross coupling with aryl boronic acids, [25] methanolysis with sodium acetate, [23] and substitution with diverse nucleophiles [26] have all been demonstrated with the −CF 2 Cl group in previous literature. The chlorodifluoromethyl group has also been demonstrated as a valuable precursor for late‐stage selective radiolabeling with nucleophilic 18 F sources [27] .…”
Section: Introductionmentioning
confidence: 82%